2015
DOI: 10.1590/01047760201521021532
|View full text |Cite
|
Sign up to set email alerts
|

Estimação De Volume De Madeira De Eucalipto Por Cokrigagem, Krigagem E Regressão

Abstract: No semiárido pernambucano na região do Polo Gesseiro do Araripe, onde é produzido 97% do gesso consumido no Brasil, um experimento florestal com 1875 árvores de eucaliptos foi cortado e todas as árvores foram cubadas rigorosamente pelo método de Smalian. A localização de cada árvore foi demarcada num plano cartesiano, e uma amostra de 200 árvores foi retirada pelo processo inteiramente aleatório. Nas 200 unidades amostrais foram utilizados três métodos de estimação para a variável volume de madeira, análise de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
(1 reference statement)
0
8
2
7
Order By: Relevance
“…In studies with the species Quercus suber in Spain, Montes et al (2005) observed that when the basal area presented spatial continuity, random sampling has a greater standard error than systematic sampling. Contrary results have been observed by Lundgren et al (2015) in Eucalyptus stands in the semiarid of Pernambuco, where random sampling showed the best results for estimating the individual eucalyptus volume performed by the geostatistical analysis. Thus, it is observed that spatial continuity is influenced by the different forest physiognomies, in addition to the various methods and sampling intensities.…”
Section: Comparison Between Traditional and The Geostatistical Interpcontrasting
confidence: 84%
“…In studies with the species Quercus suber in Spain, Montes et al (2005) observed that when the basal area presented spatial continuity, random sampling has a greater standard error than systematic sampling. Contrary results have been observed by Lundgren et al (2015) in Eucalyptus stands in the semiarid of Pernambuco, where random sampling showed the best results for estimating the individual eucalyptus volume performed by the geostatistical analysis. Thus, it is observed that spatial continuity is influenced by the different forest physiognomies, in addition to the various methods and sampling intensities.…”
Section: Comparison Between Traditional and The Geostatistical Interpcontrasting
confidence: 84%
“…The existence of spatial dependence for plot volume was verified by the experimental spherical semivariogram, using the Geostatistical Analyst tool of ArcGIS 10.1 software. It was represented by the formula: Y(h) = C0 + C x [1.5 (h/A)-0.5(h/A)³]; wherein Y(h) = theoretical semivariance, C0 = nugget effect, h = distance, C = sill, and A = range (Lundgren et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous methodologies created or developed to characterize the pattern of spatial distribution of tree species. Among these methodologies, the geostatistics (Kriging interpolation) techniques have been highlighted in forest studies and their use has been increasing in recent years (Amaral et al, 2013;Valtera et al, 2013;Lundgren et al, 2015;Zhang et al, 2015). Kriging interpolation is a method that uses the position information of the sample and the value that the variable assumes at each point.…”
Section: Introductionmentioning
confidence: 99%